"Am I Masculine Enough?": Queer Filipino College Men and Masculinity. Issue 1 (2nd January 2017) - Chan, Jason
Abstract : Research on college men and masculinities has been of interest within higher education, yet there is limited focus on the experiences of students with multiple marginalized identities. Through semi-structured interviews with gay, bisexual, and queer Filipino undergraduate men, this study examined how students defined, understood, and experienced masculinity, with emphases on the influence of environmental factors within family, cultural, and campus contexts. Overarching themes and implications for student affairs practice are discussed.